Bioefficacy of Lecanoric Acid Produced by Parmotrema austrosinense (Zahlbr.) Hale against Tea Fungal Pathogens - Kalidoss Rajendran; Ponnusamy Ponmurugan; Balasubramanian Mythili Gnanamangai; Ponmurugan Karuppiah; Mohammed Rafi Shaik; Mujeeb Khan; Merajuddin Khan; Baji Shaik (Horticulturae, 2023)
Lichens are symbiotic organisms that are composed of fungal partners and photosynthetic algal partners. During the symbiotic process in lichen thallus, the fungus synthesizes certain secondary metabolites in which lecanoric acid is very important in terms of antibiotic properties. Considering the vital importance of lecanoric acid, the present study aimed to produce lecanoric acid from the thallus of Parmotrema austrosinense lichen using Modified Bold’s basal salt medium and evaluate the bio-efficacy against tea fungal pathogens. Lecanoric acid was purified and confirmed by micro-crystallization method and subsequently bioassayed against tea fungal pathogens. The results revealed that lecanoric acid registered a significant antifungal activity in terms of the growth inhibition of test pathogens. Companion systemic and botanical fungicides were found to be inferior to lecanoric acid in the percentage of growth inhibition. The inhibition rate varied among tea pathogens. Of the tea pathogens tested, tea leaf disease-causing pathogens including Cercospora theae (C. theae), Glomerella cingulata (G. cingulate), and Phomopsis theae (P. theae) showed the highest percentage of growth inhibition followed by stem and root rot diseases. The present study suggests that lecanoric acid showed an inhibitory effect against tea pathogens, which might be due to antibiotic properties and fungicidal action of lecanoric acid.